FAULT SEAL ANALYSIS ON RESERVOIR OF GUMAI FORMATION AND BATURAJA FORMATION IN NORA FIELD, SUNDA BASIN - R. N. TAMPUBOLON, GREGORY
Nora field, Sunda Basin is a hydrocarbon field which located in offshore South East Sumatra and operated by PT Pertamina Hulu Energi Offshore South East Sumatra (PHE OSES). Nora field consist of continental sediment, shallow marine sediment, and deep marine sediment, with the main reservoir is Gumai Formation and controlled by normal fault with the direction northeast (NE)-southwest (SW). These faults can act as traps or hydrocarbon migration path. This research is conducted to analyze the characteristic of normal fault seal in Nora Field using the Shale Gouge Ratio (SGR) method. The data used are 3D seismic data with an area of 40.166 km2, data from 12 wells and the result of the Drill Stem Test (DST) pressure test. This research focused on the reservoir of the Gumai Formation and the Baturaja Formation, with the assumption that the Shale Gouge Ratio (SGR) method can be used in carbonate lithology and gamma ray log data can represent the description of clay volume (vclay) in carbonate rocks. The analysis was carried out by making a juxtaposition diagram, a vertical fault throw diagram, a clay volume (vclay) diagram and a Shale Gouge Ratio (SGR) diagram in the fault plane. The result of normal fault analysis in Nora Field show the dominance of juxtaposition of claystone with limestone lithology and limestone with limestone, the value of the vertical shift of the fault (throw) with a range of 25-300 feet, clay volume (vclay) with a dominant value of 0.02 and 0.98, and the Shale Gouge Ratio (SGR) with a dominant value of 0.2-0.6. Based on Drill Stem Test (DST) pressure data on the Nora Field, in SSTVD (2899 ft – 2991 ft), there is the pressure difference about 18,6 psi – 56,1 psi and the difference in the depth of Lowest Known Oil (LKO) in the Baturaja horizon reservoir (footwall) and Gumai Carbonate (hangingwall) horizon reservoir. It indicates that there is no fluid communication between the juxtaposition of the reservoir. The characteristic of the normal fault seal in the Nora Field has been being controlled by the lithology juxtaposition and the presence of clay material in the fault zone.